Exploring Junior High School Students’ Environmental Care Attitudes through Science Learning: Towards a Green Mindset Development - Ikhsan, Muhammad; Atun, Sri; Pamungkas, Oky (Universitas Tidar, 2025)
Cultivating an environmental care attitude among students is essential to support sustainable development and environmental protection. This study aims to explore junior high school students’ environmental care attitudes within the context of science learning on global warming. A quantitative descriptive design was employed involving junior highschool students. Data were collected using a validated questionnaire with a prosocial intention scale covering four indicators: energy saving, waste management, carbon emission reduction, and environmental care. Descriptive statistical analysis was used to determine the mean and percentage of each indicator. The results revealed that the overall level of students’ environmental care attitude was 78% (good category). Among the indicators, energy saving (86%) and environmental care (89%) were in the very good category, while waste management (65%) was categorized as adequate and carbon emission reduction (73%) as good. These findings indicate that students show strong awareness of energy use and cleanliness but limited responsibility for waste processing and reducing emissions. It is recommended that science learning be integrated with practical environmental education programs to strengthen students’ green mindset and sustainable behaviors in daily life.